1969
DOI: 10.1099/00221287-57-2-227
|View full text |Cite
|
Sign up to set email alerts
|

Thioguanine-dependent Light Sensitivity of Perithecial Initiation in Sordaria fimicola

Abstract: S U M M A R YPerithecial initiation is strongly inhibited by visible light in less than 18-hr-old hyphae of Sordariajimicola which are grown in the presence of I p~-6-thioguanine. It is known that 6-thioguanine is destroyed when exposed to light in vitro with oxygen and a sensitizing dye like methylene blue is present. The most effective wavelength region for perithecial inhibition is the blue region, indicating that possibly flavins are the photosensitizing compounds in this case. The synthesis of carotenoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1970
1970
1977
1977

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In Hypomyces solani f. cucurbitue (CURTIS, 1964) and Diaporthe phuseolorum var. batatatis (TIMNICK,et al,195 1) a photoinhibitory effect was observed but the state of hyphal tip growth was not stated, and in Sorduriu firnicolu (SURAPIPITH and LINDENMAYER, 1969) this effect was observed while the tip was growing, although responses to light after the tip of hyphae reached the other end of the growth tube were not mentioned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Hypomyces solani f. cucurbitue (CURTIS, 1964) and Diaporthe phuseolorum var. batatatis (TIMNICK,et al,195 1) a photoinhibitory effect was observed but the state of hyphal tip growth was not stated, and in Sorduriu firnicolu (SURAPIPITH and LINDENMAYER, 1969) this effect was observed while the tip was growing, although responses to light after the tip of hyphae reached the other end of the growth tube were not mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…butututis (TIMNICK,et al,195 1) It is common for sporulation to commence when the mycelium of a colony growing in artificial culture reaches the edge of the petri dish (HAWKER, 1966). In Pleuruge setosu (CALLAGHAN, 1962) and Sorduriufimicolu (SURAPIPITH and LINDENMAYER, 1969), the effect of light on perithecial formation was investigated while the hyphal tip was growing. However, no studies have been reported on the interaction between the effect of light on perithecial formation and the state of hyphal tip growth.…”
Section: Environmental Factors Influence Fungal Reproduction (Hawkermentioning
confidence: 99%
“…In some cases it might be desirable to have multiple sets of rules. An example can be TOL-system found in [SL69], where growth behaviour in light is different from the one in darkness. An extension to OL-systems proposed by Rozenberg are table L-systems, also TOL-systems [Roz73].…”
Section: L-systemsmentioning
confidence: 99%